Comparison of Efficacy of Different Bio-Enzyme on Acidic Soil - Mishra, Jyoti Jayprakash; Gore, B.M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
An increase in population increases the demand for food sources, which creates pressure on agriculture. As a result, more synthetic fertilizers are used. Because of the inevitable use of synthetic fertilizer, the nutrient content in soil decreases. Bio-enzymes are a good alternative to synthetic fertilizers, As they increases the micro and macronutrients of the soil. Bio-enzyme works as a stimulator that stimulates the plant growth. It is cost-effective and helps in breaking down the complex compound into simple ones. In this experiment, acidic soil is treated with citrus, mixed fruits, vegetable bio enzyme, and organic fertilizer. The test is done in six samples such as control (C), BE1(C), BE1(D), BE2(C), BE2(D), and OF (Organic fertilizer). After the treatment, the pH of the soil increases from 4.5 to 6.5. the NPK value of soil also increases Kg/acre in 40 days. The organic carbon (OC) content of the soil increases from 0.4 to 0.9%. The moisture content of the soil increases gradually. Adding the bio enzyme into the acidic soil helps to maintain the pH of soil between 6.2 to 6.8 for proper growth of plants. Besides also increases the NPK value of soil and also maintains the percentage of OC.